Comparison of Attachment Problems in Romantic Relationships Between Individuals with Bipolar Diagnosis and Individuals Without a Known Psychiatric Diagnosis - Aliş, Nisa (Advances in Social Sciences Research Journal, 2022)
Parenting Styles, Attachment Styles, Loneliness as a predictor of Relationship satisfaction Attachment is when one forms a deep and lasting emotional connection to one another across time and space. Attachment is not always mutual. It is also possible to connect to a person unrequitedly. The bond that an individual has with the people in his life is related to attachment styles in infancy. There has been postulation about the connection between bipolar and attachment problems, and several studies have been done on the relationship between anxiety, depression, and relationship satisfaction in general but due to the scarcity and unavailability of bipolar patients, few studies have been conducted. Hence this study aimed to examine the relationship between attachment styles, parenting styles, loneliness, and romantic relationship satisfaction among individuals diagnosed with bipolar disorders and people without the diagnosis. One hundred and sixty-nine people participated in this study. Parenting styles were examined using the Parenting Authority Questionnaire (PAQ), The Experience in Close Relationships questionnaire was used to evaluate the attachment style, UCLA Loneliness Scale measured loneliness and the Relationship Scales Questionnaire (RSQ) evaluated the relationship satisfaction. Results of the multiple regression showed that there was a collective significant relationship between, loneliness, attachment styles, and relationship satisfaction.Also, a significant negative relationship between Avoidance Attachment and romantic relationship satisfaction and also a significant negative relationship between Anxiety Attachment and romantic relationship satisfaction were found. But no significant relationship between parenting styles and romantic relationship satisfaction.